Development of a Novel Multiplex Immunoassay Multi-cruzi for the Serological Confirmation of Chagas Disease. - Elodie Granjon; Marie-Laure D; Esber Saba; Ester Sabino; Lea Campos de Oliveira; Maan Zrein (Public Library of Science (PLoS), 2016)
BACKGROUND:Chagas disease is due to the parasite Trypanosoma cruzi, a protist disseminated by a Triatome vector. This disease is endemic to Latin America and considered by WHO as one of the 17 world's neglected diseases. In Europe and in North America, imported cases are also detected, due to migration of population outside of the endemic region. Diagnosis of T. cruzi infection is usually made indirectly by the detection of specific antibodies to T. cruzi antigens. Following initial diagnostic evaluation or screening test (qualifying or discarding blood donation), a confirmation test is performed for samples initially reactive. The test presented in this study aims at the confirmation/refutation of the infectious status of human blood samples and will permit taking appropriate clinical measures. METHODOLOGY/PRINCIPAL FINDINGS:We designed a novel array of twelve antigens and printed these antigens onto 96-well plates. We tested 248 positive samples T. cruzi, 94 unscreened blood donors' samples from non-endemic area, 49 seronegative blood donors, 7 false-positive and 3 doubtful samples. The observed reactivities were analyzed to propose a decision-tree algorithm that correctly classifies all the samples, with the potential to discriminate false-positive results and sticky samples. We observed that antibodies levels (Sum of all antigens) was significantly higher for PCR positive than for PCR negative samples in all studied groups with Multi-cruzi. CONCLUSION/SIGNIFICANCE:The results described in this study indicate that the Multi-cruzi improves the serological confirmation of Chagas disease. Moreover the "sum of all antigens" detected by Multi-cruzi could reflect parasitemia level in patients-like PCR signals does-and could serve as an indicator of parasite clearance in longitudinal follow-ups. Validation of this assay is still required on an independent large collection of well characterized samples including typical false-reactive samples such as Leishmaniasis.